Economic Empowerment of Peasants Victims of Agrarian Conflict Through the Production of Mocaf Flour in Mekar Jaya Village, Wampu Subdistrict, Langkat - Sinaga, Randa Putra Kasea; Berlianti (Talenta Publisher, 2023)
Peasants victims of agrarian conflict located in Mekar Jaya Village, Wampu Subdistrict, Langkat Regency formed a cooperative as a container for improving economic conditions. However, they still have problems running a business, such as a lack of understanding and experience in trying. Based on the partners' problems, the solution offered in this service is to intervene in the economic empowerment of Peasants through the production of Mocaf flour, which is hopefully to impact the increasing economy of Peasants independently. The proposed activity plan is Business Management Education, Mocaf Flour Making Training, Marketing Strategy Education, and Cooperative Business Unit Monitoring.